Rancang Bangun Sistem Informasi Geografis Pendataan Jalan di Kabupaten Garut Berbasis Web - Fitri Nuraeni; Raden Erwin Gunadhi Rahayu; Moch. Lutfhi Waliyul Fahmi (Jurnal Algoritma, 2023)
Roads can be said to be a transportation infrastructure that connects one place to another. Roads of different lengths have different surface layers and their respective conditions. At present the road data collection carried out by the Public Works and Spatial Planning Office (PUPR) is still being carried out by inputting and storing data that is still written in the document. Based on this problem, the Geographic Information System is one of the solutions that can be used, this system will later become a service tool for the Office (PUPR) in collecting data and converting spatial data into digital maps to make it easier to visualize road conditions to the public. The methodology used is the Rational Unified Process with the stages or phases in it, while the application development uses the Laravel framework and the mapping uses Leaflet JS. The results of this study obtained a Web-Based Road Data Collection Graphic Information System. This system is expected to be able to assist the Office (PUPR) when working on road data collection and visualizing road conditions to the public.